Circular RNA-regulated autophagy is involved in cancer progression - Zhou, Xuejian; Lin, Juntao; Wang, Feifan; Chen, Xianwu; Zhang, Yan; Hu, Zhenghui; Jin, Xiaodong (Frontiers in Cell and Developmental Biology, 2022)
Circular RNAs (circRNAs) are a sort of long, non-coding RNA molecules with a covalently closed continuous ring structure without 5'-3' polarity and poly-A tail. The modulative role of circRNAs in malignant diseases has been elucidated by many studies in recent years via bioinformatics and high-throughput sequencing technologies. Generally, circRNA affects the proliferative, invasive, and migrative capacity of malignant cells via various mechanisms, exhibiting great potential as novel biomarkers in the diagnoses or treatments of malignancies. Meanwhile, autophagy preserves cellular homeostasis, serving as a vital molecular process in tumor progression. Mounting studies demonstrated that autophagy can not only contribute to cancer cells survival but also induce the autophagic cell death in specific conditions. A growing number of researches have indicated that there existed abundant associations between circRNAs and autophagy. Here we systemically reviewed and discussed recent studies on this topic in different malignancies, and concluded that circRNA-autophagy axis played crucial roles in the proliferation, metastasis, invasion, drug or radiation resistance of different tumor cells.